2022
DOI: 10.3390/su14052714
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Corporate Energy Management Systems and Voluntary Carbon Information Disclosure in Chinese Listed Companies: The Moderating Role of Corporate Leaders’ Low-Carbon Awareness

Abstract: The “Energy-Saving and Low-Carbon Action Implementation Plan for Ten Thousand Enterprises” urged Chinese energy users to establish an energy management system (EEM) that emphasizes energy conservation and emission reduction. This study applied the voluntary information disclosure theory, stakeholder theory, and legitimacy theory to construct a research framework for corporate voluntary carbon information disclosure (CID) under combined action of disclosure decision, EEM related to carbon information collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
1
4
0
Order By: Relevance
“…This shows that companies in energy-intensive industries, which have been anticipated by society and stakeholders, have higher operations and disclosures of energy conservation. This is consistent with previous studies indicating that companies in environmentally or energysensitive industries disclose more information on environment or energy conservation than lower sensitive industries [1,23,24,65].…”
Section: Descriptive Statisticssupporting
confidence: 92%
See 2 more Smart Citations
“…This shows that companies in energy-intensive industries, which have been anticipated by society and stakeholders, have higher operations and disclosures of energy conservation. This is consistent with previous studies indicating that companies in environmentally or energysensitive industries disclose more information on environment or energy conservation than lower sensitive industries [1,23,24,65].…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…Stakeholder theory integration may not be complete without the critical insights offered by legitimacy theory [20]. Legitimacy theory explains the motivation of businesses through the lens of society's expectations by considering whether the company has met or exceeded the expectations of society [24]. This theory views an organization as a part of a larger system that, if expectations are not met, leads it to lose access to resources or even cease to exist.…”
Section: Legitimacy Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous approaches to determining the maximum power point of PV modules [17]. There are two types of algorithms: direct algorithms and indirect algorithms.…”
Section: Mppt Algorithms For the Pv Systemmentioning
confidence: 99%
“…In terms of the relationship between low carbon awareness and carbon disclosure, Qi Xiaoyan (2012) concluded that the importance of environmental protection by company management and the establishment of an environmental protection department were positively related to the level of carbon disclosure by the company. Pan An E and Guo Qiushi (2018) concluded that the stronger the environmental awareness of executives, the higher the level of corporate environmental information disclosure 22 Dan E & Shen J (2022) used A-share listed companies from 2009-2017 as a research sample and used voluntary disclosure theory, stakeholder theory and legitimacy theory to construct a research framework and found that leaders' low carbon awareness has a facilitating effect on voluntary corporate carbon information disclosure 36 .…”
Section: Low Carbon Awareness Related Researchmentioning
confidence: 99%